Comprehensive Environmental Impacts and Optimization of Onshore Shale Gas Development and Delivery. Issue 5 (24th April 2019) - Bista, Sangita; Jennings, Philip; Anda, Martin
Abstract : The environmental impact of shale gas hydraulic fracturing is not completely understood. Therefore, the objective of this paper is to estimate the lifecycle environmental impact of shale gas production per mega joule (MJ) of energy extracted and delivered. The analysis is based on using CML 2001‐Apr 2015 methods in GaBi software on a case study of a shale gas well. The global warming potential (GWP100) ranges from 54 to 99 g CO2 e /MJ with a central estimate of 72 g CO2 e /MJ. The GWP 100, including land use change, is 230 g CO2 e /MJ. The best‐case scenario, with no venting of the gas, has the minimum GWP 100 impact. Shale gas has a high marine ecotoxicity potential, among other environmental impacts. Bentonite contributes the most to the abiotic depletion potential elements impact. The frac water contributes the most to the freshwater aquatic ecotoxicity potential (FAETP) impact. Mercury (Hg) and radioactive elements (e.g., radon) are the major pollutants contributing to the terrestrial ecotoxicity potential impacts. The findings of this study can be used for optimization of the processes used by mining and exploration companies. Abstract : Product optimization is identifying hotspots to minimise their impacts! Lifecycle assessment is used to achieve optimization in environmental engineering. This work provides ways to optimise an onshore gas extraction system. It investigates all the major environmental impacts including the land use change. Sensitivity analysis and Monte Carlo analysis validates the robustness of this scientific research.